PENGEMBANGAN LABORATORIUM MINI BANK EKONOMI SYARIAH MENJADI INCOME-GENERATING UNIT - Bekti Widyaningsih (Universitas KH. A. Wahab Hasbullah, 2020)
Sharia financial institutions in Indonesia are increasingly in demand. This is evidenced by developments that have increased every year. As seen in June 2020, the growth of Islamic banking in Indonesia has reached 9.22% or 545.39 trillion, an increase in profit compared to 2019. The growth of financial institutions Sharia that applies Sharia principles is not only in the scope of banking but also non-bank financial institutions (LKBB) such as Sharia insurance, Sharia securities, Sharia pawnshops, Sharia microfinance institutions better known as Baitul Maal wa Tamwil (BMT), and so. This phenomenon is what motivates Wahab Hasbullah University (Unwaha) Jombang to provide the infrastructure needed for academics, both teachers and students. In this case, Unwaha provides a sharia banking laboratory to support Islamic Economics teaching and learning activities. Not only as an infrastructure that facilitates the academic field, but the role of this mini bank can be developed into an income-generating unit or unit that can generate its own profit by opening financial services specifically for students, lecturers, and employees. Therefore the ES Unwaha mini bank Laboratory needs to think about activities that can generate income from the ES Unwaha mini bank Laboratory or income-generating activities. Mini bank laboratory activities that are specific can be